Computational investigation unveils pathogenic LIG3 non-synonymous mutations and therapeutic targets in acute myeloid leukemia - Md. Arif Hossen; Umme Mim Sad Jahan; Md. Arju Hossain; Khalid Hossain Asif; Ahona Rahman; Sabbir Ahmed; Md. Moin Uddin; Md Faisal Amin; Muhammad Abdul Barik; Mohammod Johirul Islam; Mohammad Kamruzzaman; Soharth Hasnat; et al. (PLoS ONE, 2025)
Single nucleotide polymorphisms (SNPs) in DNA repair genes can impair protein structure and function, contributing to disease development, including cancer. Non-synonymous SNPs (nsSNPs) in the LIG3 gene are linked to genomic instability and increased cancer risk, particularly acute myeloid leukemia (AML). This study aims to identify the most deleterious nsSNPs in the LIG3 and potential therapeutic targets for DNA repair restoration in AML. We employed different computational approaches to analyze LIG3 nsSNPs and pathogenicity. Subsequently, molecular docking, molecular dynamics simulation (MDS), gene expression and clinical validation of LIG3 were performed to evaluate ligand-binding affinities, protein stability and to identify discriminatory gene signatures. Out of the 12,191 mapped SNPs, 132 were nsSNPs located in the coding region. Among these, 18 nsSNPs were identified as detrimental including 12 destabilizing and 6 stabilizing nsSNPs. Nine cancer-associated nsSNPs, including L381R and R528C, were predicted due to their structural and functional impacts. Further analysis revealed key phosphorylation and methylation sites, such as 529S and 224R. MDS highlighted stable interactions of compounds AHP-MPC and DM-BFC with wild-type and R528C mutant LIG3 proteins, while R671G and V781M mutants showed instability. Protein-protein interaction networks and functional enrichment linked LIG3 to DNA repair pathways. Kaplan-Meier analysis associated high LIG3 expression with improved survival in breast cancer and AML, suggesting its role as a prognostic biomarker. This study emphasizes the mutation-specific effects of LIG3 nsSNPs on protein stability and ligand interactions. We recommend identifying DM-BFC to advance personalized medicine approaches for targeting deleterious variants, following in-vitro and in-vivo validation for AML treatment.